Association of sleep characteristics with renal function in menopausal women without recognized chronic kidney disease - Tong, Jianqian; Li, Changbin; Hu, Jiangshan; Teng, Yincheng; Zhou, Yang; Tao, Minfang (Frontiers in Psychiatry, 2022)
Objective: To delineate the association between sleep characteristics and renal function in peri-postmenopause free of CKD as well as cardiometabolic and hormone indicators. Methods: Cross-sectional data from 823 peri-postmenopausal women were analyzed through the Pittsburgh Sleep Quality Index (PSQI) and serum cystatin C (Cys-C). Logistic regression models were used to assess the association between cumulative/each sleep parameter and renal function after adjusting for cardiometabolic variables. Results: After confounding factors, we identified that poor perceived sleep quality, shorter sleep duration(<6 hours), low sleep efficiency (<75%), delayed sleep latency and worse sleep disturbance elevated more than doubled the odds ratio for declining renal function(≥0.91mg/dl, the highest Cys-C) in postmenopause in a graded fashion. Meanwhile, multiple logistic regression analysis revealed that sleep disorder (PSQI ≥ 8) ,late postmenopause, highest quartile independently increased the odds ratio for declining renal function (OR 2.007, 95% CI 1.408-2.861, OR=3.287, 95%CI: 3.425-8.889, OR=2.345, 95% CI: 1.310-4.199, respectively)，while participants with menopausal hormone replacement (MHT) lower the odds of declining renal function (OR=0.486, 95% CI:0.324-0.728). Conclusions: The findings proposed that maintaining good sleep quality should be attached great importance to postmenopausal women, which provides clinical evidence for the feasible early detection and effective prevention such as MHT of renal disease progression in postmenopausal women.